Pelaksanaan Pengarsipan Berkas Dalam Divisi Finance PT Dimensi Citra Semesta - Eries Priandana Putra; Maharani Ikaningtyas (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
This research aims to analyze the implementation of file archiving in the finance division of PT Dimensi Citra Semesta. The research utilizes a qualitative descriptive research method with data collection techniques including case studies, observation, interviews, and documentation. The results of this research indicate that the implementation of file archiving in the finance division of PT Dimensi Citra Semesta involves six steps: receipt, verification, numbering, grouping, storage, and file disposal. The file archiving process aligns with the ISO 15489-1:2016 standard on records management. The file archiving tools in the finance division of PT Dimensi Citra Semesta consist of both physical and electronic tools. Archiving challenges in the finance division of PT Dimensi Citra Semesta are divided into two categories: internal challenges and external challenges. Internal challenges originate from within the finance division itself, such as space limitations, file damage, input errors, file loss, and others. External challenges come from outside the finance division, such as inappropriate file requests, delayed file deliveries, file format mismatches, and others.